Sentinel event reviews in the criminal justice system: a review of the literature - Friend, Karen B. (Criminal justice studies, 2020)
Trust between law enforcement officers and the communities they serve is essential to the safety of our citizens. Relationships between police and communities have, however, become increasingly strained, with reports of deadly events and wrongful convictions filling the television, newspapers, and the Internet. While the model of conducting internal investigations to determine blame and penalize the individuals involved has been used for years, a new paradigm to bring systemic change is increasingly being embraced by the criminal justice field. Historically used in other disciplines, sentinel event reviews have been employed to understand organizational failures. Multiple key community stakeholders gather to conduct a root cause analysis, which is an empirical approach that involves data collection to understand the systems-level causes of organizational events. The purpose of this paper is to examine the literature on sentinel event reviews in the criminal justice system, borrowing heavily from other disciplines where they are already well-established. We then examine the literature on organizational adoption, since the ultimate goal of sentinel event reviews is to lead to stronger systems that can learn from systemic mistakes and allow the dissemination of best practices to benefit both law enforcement and the individuals they serve.